Pragmatic analysis of Invisibles. Voces de un trozo invisible de este mundo by Juan Diego Botto - del Río Zamudio, Sagrario (Oltreoceano - Rivista sulle migrazioni, 2024)
The aim of this article is to carry out a pragmatic analysis of Juan Diego Botto's play Invisibles. Voces de un trozo invisible de este mundo, in which the author confronts two themes that many people must face for different reasons: exile (which he himself suffered) and emigration. In our case, we will focus more on the former and comment on the types of exile that exist, as well as some related words such as deportation, expatriation, expulsion, or estrangement, etc. In fact, although in dictionaries they appear as synonyms, but they are not exactly the same because exile is the separation from the land where one lives, while banishment is the result of a penalty imposed, usually by the State, and whose purpose is the expulsion of a person from a place or territory for having committed a crime, it can be temporary or sine die (there is also talk of expulsion and there are well-known cases in Chile –they chose the place to go –and Argentina– expulsion of foreigners convicted of a crime in that country, provided that they had served half of their sentence and without open legal proceedings–). Another type of separation was caused by Italian fascism whereby many intellectuals were confined or forced to live in southern areas or on Mediterranean islands. Today, two writers live under escort outside their respective countries: Salman Rushdie and Roberto Saviano. On the other hand, one people that has experienced expulsion, exodus and diaspora is the Jewish people. The expulsion, during the reign of the Reyes Católicos (with Felipe III, the expulsion of the moriscos or descendants of Muslims), the exodus, after the Second World War and the diaspora when this people voluntarily disintegrated outside the borders of Palestine. Methodologically, with a Pragmatic approach, we will examine the illocutionary force of some fragments, paying special attention to the satisfactory respect of Grice's maxims or other of his lines of research such as Austin's speech acts, etc.